PERBEDAAN HASIL BELAJAR IPAS DAN KERJASAMA PESERTA DIDIK KELAS 3 MENGGUNAKAN MODEL PEMBELAJARAN TALKING STIK DAN MODEL PEMBELAJARAN DRAGON BALL DI SD NEGERI KLIMAS - Nicolaus Christian Adi Saputra; Kristin, Firosalia (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This experimental study aims to determine whether there is a significant difference in the application of the Talking Stick learning model and the Dragon Ball learning model on the results of learning science and the ability of cooperation of grade 3 elementary school students. The research design used in this study is Nonequivalent Control Group Design. The population used in this study is Elementary Schools located in the Prawirosekti Cluster in Karanggede District, Boyolali Regency, Central Java. The schools used as research are Klimas Elementary School and Sranten 1 Elementary School. The sample in this study was grade 3 students of Klimas Elementary School as the experimental class, and grade 3 students of Sranten 1 Elementary School as the control class. The data collection technique used in this study was observation and testing. With data analysis techniques in the form of normality tests, homogeneity tests, and difference tests using the t-test (independent sample t-test) with the help of SPSS 24. The results of the study showed a significant level (2-tailed) of 0.001 <0.05, so Ho was rejected and Ha was accepted. Ha stated that the results of learning science and cooperation of grade 3 students using the Talking Stick learning model had a significant effect compared to using the Dragon Ball model. This is also supported by the average value of the experimental class which had an average value of 80.28. While the control class had an average value of 72.16. From these results, it shows that the results of learning and cooperation of students using the Talking Stick learning model are better than the Dragon Ball learning model.